Data and policy scale mismatch in coastal systems : The potential of μUAS as new tools for monitoring coastal resilience - Graves, Scott M. (Towards Coastal Resilience and Sustainability, 2018)
An important challenge in monitoring, planning and evaluating coastal saltmarsh resources in the face of predicted sea level rise (SLR) using numerical
Keywords: 3D modeling; Antennas; Coastal systems; Flight planning; Model results; Numerical models; Remotely sensed data; Scale mismatches; Sea level; Sea level rise; Structure from motion; Unmanned aerial systems; Unmanned aerial vehicles (UAV); Wetlands; dept.egm

Examining historical land management and current urban forest health - Massa, Amanda; Zavar, Elyse; Lavy, Brendan L.; Graves, Scott M. (Northeastern Geographer, 2018)
Urban forests can serve as valuable oases for birds and other wildlife in densely-populated urban and suburban areas with proper management. This study analyzes forest health and habitat availability of a publically-owned urban forest in West Haven, Connecticut. During the first half of the twentieth-century, this urban forest was privately-owned and primarily managed as an orchard and meadow for grazing horses. By the mid-twentieth-century, farming dwindled on the land and vegetation overtook the property. Today, this closed-canopy forest, with access to both freshwater streams and marshlands, provides habitat to a variety of native and invasive plant and animal species. By identifying the forest species and characteristics of the six hectare Cove River Historic Site (CRHS) urban forest, this study serves as the first forest inventory and provides a baseline dataset to help manage an ecologically important urban forest. Additionally, we identified bird habitat opportunities and bird species at the property. This study considers both the historic land management practices of this site in tandem with present-day forest health and animal activity to understand how this fragmented forest contributes to local biodiversity. The results indicate that this property, located within the urban environment of the central Connecticut coastline, offers varied habitats and food sources for many resident and migratory bird species, as well as wildlife including foxes.
Keywords: BIRD habitats; FOREST health; LAND management; MIGRATORY birds; URBAN forestry; bird habitat; conservation; dept.egm; invasive species; land management; peer-reviewed; urban forestry; ⛔ No DOI found